Grammatical linkage and its effect on textual cohesion (Al-Hajjaj bin Yusuf Al-Thaqafi for the people of Iraq as a model) - Ahmed, Isrra Ghanim (Al-Adab Journal, 2022)
Linking occupies a prominent position in the linguistics of the text, as it is one of the things that textual scholars have been interested in in their research; Because it achieves coherence and formal cohesion in the surface structure, with multiple different relationships that link the words of one sentence and the sentences of one text, making it an integrated whole that is not dispersed by phrases and meanings. The researcher dealt with this issue in the speeches of Al-Hajjaj bin Yusuf to the people of Iraq, and his relationship is characterized by violence, oppression and severe prejudice against them in his sermons. There is a variety of use in these links, and the phenomenon of linkage has a clear impact on textual cohesion and harmony, and it is not isolated from the concepts and terms in “traditional grammar” “towards the sentence.” Linking from a perspective towards the text and towards the sentence; Because of the existence of a relationship between them, referring to the opinions of grammarians and the positions of scholars, and the use of linking with tools, linking with context, then linking with referrals, then the study concluded with a conclusion in which the most prominent results were.